PHYSIOLOGICAL RESPONSE OF SWEET CORN PLANTS OF THE TALENTA VARIETY AFFECTED BY MANGANESE (Mn) SUPPLY DURING THE GROWTH PHASE - Novrimansyah, Eko Abadi (International Journal of Multidisciplinary Reseach, 2025)
Manganese is one of the eight essential microelements for plants that are needed in the right amounts to achieve normal growth and yields. Manganese is involved in a number of physiological and metabolic processes of plants such as enzyme activation, protein synthesis, carbohydrate metabolism, lipids, auxin, nucleic acids, gene expression, and the development of reproductive organs. Micronutrients play a role in every phase of plant life starting from seeds, plant vegetative growth, and plant photosynthesis processes. The purpose of this study is to determine the role of Manganese in plant physiology starting from seed germination, plant growth and the rate of photosynthesis at the greening level of leaves. This study includes 4 treatments, namely P1 (Control), P2 (Priming), P3 (Spray), P4 (Priming + Spray). The experiment used a complete random design with each treatment repeated 3 times. The total experimental unit in this study is 12 tiles. The observation variables of this study are germination, plant height, number of leaves, and photosynthesis rate at the greenery level of leaves. Based on the results of the study, it is known that feeding at a concentration of 50 ppm with the p4 method (Priming + Spray) is able to increase germination, vegetative growth of plants and the greenness of plant leaves compared to other treatments. . These results show that the application of Manganese, especially through the priming + spray method of leaves, is effective in optimizing the initial phase of germination, growth and photosynthesis rate at the greening level of maize plant leaves.